Real-Time Monitoring of Dissection Events of Single Budding Yeast in a Microfluidic Cell-Culturing Device Integrated With Electrical Impedance Biosensor - Zhu, Zhen; Geng, Yangye; Wang, Yingying; Liu, Ke; Yi, Zhenxiang; Zhao, Xiangwei; Ouyang, Shuiping; Zheng, Ke; Fan, Yimin; Wang, Zixin (Frontiers in Bioengineering and Biotechnology, 2021)
Microfluidic devices in combination with fluorescent microscopy offer high-resolution and high-content platforms to study single-cell morphology, behavior and dynamic process in replicative aging of budding yeast, Saccharomyces cerevisiae. However, a huge mass of recorded images makes the data processing labor-intensive and time-consuming to determine yeast replicative lifespan (RLS), a primary criterion in yeast aging. To address this limitation and pursue label-free RLS assays, electrical impedance spectroscopy (EIS) that can be easily functionalized through microelectrodes in microfluidic devices, was introduced to monitor cell growth and division of budding yeast. Herein, a microfluidic device integrated with EIS biosensor was proposed to perform in-situ impedance measurement of yeast proliferation in single-cell resolution so as to identify the momentary events of daughter dissection from its mother. Single yeast cells were reliably immobilized at the bottleneck-like traps for continuous culturing, during which daughter cells were effectively detached from their mother cells by hydraulic shear forces. Time-lapse impedance measurement was performed every 2 minutes to monitor the cellular process including budding, division and dissection. By using the K-means clustering algorithm to analyze a self-defined parameter “Dissection Indicator”, to our knowledge for the first time, the momentary event of a daughter removing from its mother cell was accurately extracted from EIS signals. Thus, the identification of daughter dissection events based on impedance sensing technology has been validated. With further development, this microfluidic device integrated with electrical impedance biosensor holds promising applications in high-throughput, real-time and label-free analysis of budding yeast aging and RLS.